The Influence of Marketing Mix on The Increase of Billing Sales Volume in Freedom Internet Cafe, Surakarta - Nugraha, Samuel Setya; Dewi, Adhita Maharani (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to analyze the influence of the Marketing Mix on the increase of billing sales volume at Freedom Internet Cafe, Surakarta. The hypotheses proposed in this study are as follows: H1: it is suspected that the Product influences the increase in sales volume, H2: it is suspected that Price influences the increase in sales volume, H3: it is suspected that Promotion influences the increase in sales volume, H4: it is suspected that Place influences the increase in sales volume, H5: it is suspected that the Marketing Mix influences the increase in sales volume simultaneously.The research method used is quantitative research through surveys and interviews, intended to provide explanations. Survey research takes samples from a population and uses questionnaires as the primary data collection tool. Sample selection using the stratified random sampling method is applied when the population has heterogeneous and proportionally stratified members. Therefore, this study involved 52 buyers as respondents, and data analysis was conducted using multiple linear regression models with SPSS v25 application.The data analysis results show that the t-value for the Product variable is -0.347, Price variable is 2.103, Promotion variable is 1.620, and Place variable is 2.011. Meanwhile, the t-table value is 1.677. From these research findings, it can be concluded that the Marketing Mix only affects Price and Place variables partially. Product and Promotion variables do not have a partial effect on the increase in billing sales volume at Freedom Internet Cafe. Through the F-test, it is known that the significance value is below 0.05, thus concluding that the Marketing Mix has a simultaneous effect on the increase in billing sales volume at Freedom Internet Cafe, Surakarta.